Light Emission: Spraying Light: Ambient‐Air Fabrication of Large‐Area Emissive Devices on Complex‐Shaped Surfaces (Adv. Mater. 29/2014). (August 2014) - Sandström, Andreas; Asadpoordarvish, Amir; Enevold, Jenny; Edman, Ludvig
<x xml:space="preserve">Abstract</x> Light‐emitting electrochemical cells featuring areas of 200 cm2, multicolored patterns, and light emission from 3D surfaces are fabricated in air by L. Edman and co‐workers on page 4975 using a "spray‐sintering" process developed for the purpose. Using a standard airbrush, light can be added onto a wide variety of items with complex shapes, with the realization of a luminous kitchen fork as an example. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>